"DANK" customs, bootlegs, and reworked pieces: For an expressive use defence of secondary trademark works. (19th June 2020) - Bain, Andie
Abstract: Three secondary works born from streetwear fashion have been identified, and it is the objective of this paper to elucidate why trademark use in customs, bootlegs, and reworked pieces is deserving of legal protection. The paper travels through the oppression embedded in the fashion industry, highlighting its hostility towards street associations, which provides justifications for the reappropriation of a trademark. To do so, it explores the origins of streetwear and locates it within the industry. It recognises that these secondary works sit uneasily within trademark law and free expression principles as courts fluctuate with determining the legality of their trademark use. Additionally, the interrelationship between secondary works and their online distribution reveals an existential burden on platforms to police the use of trade marks without the sufficient tools to do so. This work adopts a sociolegal approach as the topic explores the letter of the law and its implications on society and its subcultures.